Digital engagement: An investigation of how Information and Communication Technology professionals engage with technology and why digital engagement affects them differently - Spencer-Scarr, Diane Cheryl (Curtin University, 2016)
This thesis investigates the relationship between people and networked technology in order to understand the nature of this relationship and why it affects individuals differently. The research found that digital engagement is best understood as a Second Order Cybernetic system, and that engagement is directly influenced by the individuals’ level of system-‐awareness, which enables them to govern/manage their unique set of cybernetic feedback processes, both internal and external, in conjunction with their personal motivation.